Electroactive Ionic Soft Actuators with Monolithically Integrated Gold Nanocomposite Electrodes. Issue 23 (18th April 2017) - Yan, Yunsong; Santaniello, Tommaso; Bettini, Luca Giacomo; Minnai, Chloé; Bellacicca, Andrea; Porotti, Riccardo; Denti, Ilaria; Faraone, Gabriele; Merlini, Marco; Lenardi, Cristina; Milani, Paolo
Abstract : Electroactive ionic gel/metal nanocomposites are produced by implanting supersonically accelerated neutral gold nanoparticles into a novel chemically crosslinked ion conductive soft polymer. The ionic gel consists of chemically crosslinked poly(acrylic acid) and polyacrylonitrile networks, blended with halloysite nanoclays and imidazolium‐based ionic liquid. The material exhibits mechanical properties similar to that of elastomers (Young's modulus ≈ 0.35 MPa) together with high ionic conductivity. The fabrication of thin (≈100 nm thick) nanostructured compliant electrodes by means of supersonic cluster beam implantation (SCBI) does not significantly alter the mechanical properties of the soft polymer and provides controlled electrical properties and large surface area for ions storage. SCBI is cost effective and suitable for the scaleup manufacturing of electroactive soft actuators. This study reports the high‐strain electromechanical actuation performance of the novel ionic gel/metal nanocomposites in a low‐voltage regime (from 0.1 to 5 V), with long‐term stability up to 76 000 cycles with no electrode delamination or deterioration. The observed behavior is due to both the intrinsic features of the ionic gel (elasticity and ionic transport capability) and the electrical and morphological features of the electrodes, providing low specific resistance (<100 Ω cm −2 ), high electrochemical capacitance (≈mF g −1 ), and minimal mechanical stress at the polymer/metal composite interface upon deformation. Abstract : Electroactive ionic gel/metal nanocomposites are produced by implanting supersonically accelerated neutral gold nanoparticles into chemically crosslinked ion‐conductive soft polymers. The fabrication of thin (≈100 nm thick) nanostructured electrodes, with controllable electrical properties, provides high electrochemical capacitance and ionic conductivity, as well as high‐performance and long‐term durability (up to 76 000 cycles) actuation, with minimal stress at the metal/polymer interface.